ANALISIS PENGARUH IMPLEMENTASI SISTEM MANAJEMEN K3 TERHADAP PRODUKTIVITAS PEKERJA PADA PROYEK INFRASTRUKTUR - Sudarwin Hasyim; Ilham Konong; Dedi M Buamona (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2026)
Project construction bridge own risk safety and health high work safety (K3). However, the empirical relationship between the implementation of the Occupational Health and Safety Management System (OHSMS) and workers' productivity in Indonesia, especially in remote infrastructure project areas, has not yet Been Widely researched. This research analyzes the impact of implementing SMK3 on workers' productivity during bridge construction in North Maluku Province. Approach quantitative, with an explanatory design survey used. Data collected from 40 respondents using a 5-point Likert-scale questionnaire were analyzed using multiple linear regression. Five independent variables examined: K3 regulations and procedures (X1), communication workers (X2), competent workers (X3), environmental work (X4), and workers' involvement in K3 (X5). The results of the F test show that the fifth variables are, in a way, simultaneously influential on productivity among workers (F = 16.443; p < 0.05). The coefficient of determination (R² = 0.574) indicates that the model explains 57.4% of the variation in productivity. Competence worker become the most dominant factor (β = 0.307; t = 3.744; p = 0.001), followed by involvement worker in K3 (β = 0.267) and the environment work (β = 0.222). Keywords:​ System K3 Management; Productivity Workers; Project Construction Bridge; Competence Workers; Involvement of Workers.